Controlling capture plants to avoid CO2 emissions penalties during peak load demand. (March 2021) - Akram, Muhammad; Milkowski, Kris; Gibbins, Jon; Pourkashanian, Mohammed
Highlights: Four dynamic response scenarios are investigated. Overall capture efficiency can be maintained at 90 %. Emissions penalties can be lowered by plant controls. Optimisation between emissions and reboiler duty is required. Abstract: With the introduction of more and more renewables into the electricity system, pressure is mounting on the thermal power plants to operate in more flexible ways. In order to capture maximum emissions at the lowest cost, capture plants integrated with the power plants has to follow the operational regimes of the parent power plant. Therefore, capture plants has to be flexible enough to deal with the load variations on the power plants to meat grid demands. A test campaign has been carried out at the PACT 1tpd CO2 capture pilot plant to investigate capture plant flexibility in relation to power plant load variations. Monoethanolamine (40 wt.%) solvent was used to capture CO2 from gas turbine representative flue gases containing around 5% CO2 . Pressurised Hot Water (PHW) is used to regenerate the solvent in the reboiler. Four Capture plant flexibility scenarios i.e. start-up, minimum stable generation, no-stripping and over-stripping, are investigated. No-stripping tests were performed to mimic the unavailability of steam for stripping over varied periods of time by stopping PHW flow to the reboiler. The results indicate that Specific Reboiler Duty (SRD) increased by 8.7 % when the PHW stoppage time was 30 min.. Longer the PHW stoppage time, the longer it takes to recover the capture plant to the original steady state and higher the difference between the steady state capture efficiency and the average capture efficiency over the test period. For over-stripping tests, stripper pressure was reduced to 0.4 barg from the original value of 0.5 barg for a varied period of time followed by no-stripping. It was observed that longer the over-stripping period, longer the recovery time. The results indicates that SRD increased by 36 % when the over-stripping time was increased to an hour. In conclusion, it is possible to maintain 90 % overall capture efficiency, if the solvent is over-stripped for a long enough period, but reboiler duty will be increased. Optimisation of the capture process under these scenarios would be required in order to achieve a commercially-optimised balance i.e. minimum increase in SRD costs while achieving a capture efficiency that also minimises CO2 emission costs.